Domestic tourism of the urban Bengalis : a shared observation of the culture - Chatterjee, Dipankar (Array, 2008)
Summary: The research reported in this paper attempts to give an overview of the culture concerning domestic tourism of the urban Bengalis, the linguistically distinct people of India. The urban Bengalis, especially the people of Kolkata metropolis are, since colonial period, one of the largest sections of the tourists in India. This paper is an exploration of relationship between the significant Bengali representations of travel and the contemporary preferences of urban Bengali domestic tourists. With that objective, the authors, being Bengali themselves, tried to encompass and analyse all the significantly popular Bengali representation in literature, films and other agencies centred on tourism and also the real experience of the purposively selected one hundred contemporary tourists from Bengali families living in Kolkata metropolis. The former is seen to prevail as the backdrop of the later, though the later is undergoing some shifts from the former vision. The observation shows that the decision-making for the domestic tours of the Bengalis depends on the locally understood criteria of preferences and the specific operation of the criteria as actively selected by the tourists. A current account of preferences of the informants is given in order to focus on the present trends of preferred domestic tours. The approach of the work ultimately explores the repertoire of the varied, but changing cultural motivation and representation of the tourists, the continuity and change in the trends of domestic tours of the Bengalis, and other relevant issues of the local internal tourism